IDENTIFICATION OF VOLATILE COMPOUNDS IN FERMENTED MILLET BASED BEVERAGES BY GAS CHROMATOGRAPHY-MASS SPECTROSCOPY (Applied Biological Research, 2023)
Volatile compounds impart flavour in food and beverages and make the  food and food products appealing. The present study involves the development of fermented millet beverages from minor millets viz., foxtail  millet, little millet, kodo millet, proso millet and barnyard millet, by using  an isolate of Propionibacterium sp. as fermentation agent. The volatile  compounds present in the newly developed fermented millet-based  beverages were identified using hexane-extracted samples by gas chromatography-mass spectrophotometry (GC-MS). The results revealed  thpresence of 21 volatile compounds in foxtail- and proso-millets, 18  compounds in little millet and barnyard millet and 19 compounds in kodo millet. The dominant volatile compounds observed were benzene derivatives, hexadeconoic acid, acetic acid, sitosterol and octadecanoic acid in all five minor millet fermented beverages.
Keywords: Beverages; fermentation; GC-MS; millets; volatile compounds